“Bubbly heart,” a case report of Morgagni hernia delayed diagnosis in patient with Down syndrome: The hernia is in the details - Valerio D’Agostino; Giulia Valente; Emanuela Federico; Fiorentino Mondillo (Radiology Case Reports)
Morgagni hernia represents a rare form of congenital diaphragmatic hernia (2%-5%), characterized by a defect in the anterior and retrosternal diaphragm. It can be associated with other congenital anomalies, especially in conditions like Down syndrome. Symptoms are often nonspecific, and diagnosis can be missed. Imaging plays a main role in diagnosis. We describe a case of a young boy with Down syndrome suffering from fever and shortness of breath. In the appropriate clinical scenario, it is important to consider this entity among the differential diagnoses of Down syndrome patients with respiratory disease.